Zonation of Flood-Prone Areas Based on Remote Sensing Data and Hydrodynamic Models - Samsul Bachri; Arif Faisol (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Many watersheds in Manokwari are classified as flood-prone areas with a frequency of more than 1 flood per year. Limited rain stations and climate stations make it difficult to the zoning of flood-prone areas. This study aims to utilize remote sensing data and hydrodynamic models to zone flood-prone areas in watersheds (DAS). The research was conducted in the Wosi Watershed - Manokwari Regency - West Papua Province. The data used in this research is DEMNAS topographic data, Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) data acquired 1996 – 2020, Sentinel 2 imagery acquired 21 September 2020, and river maps. The peak flow in the Wosi watershed was analyzed using rational methods and flood hazard zoning was analyzed using HEC-RAS. The research showed that the Wosi River was not able to accommodate the peak flow at various return periods, consequently, the Wosi River had the potential for flooding every year. The results of this study are relevant to actual events, therefore remote sensing data and hydrodynamic models can be used to analyze peak flow and flood hazard zoning.Keywords: Climate Hazards Group Infrared Precipitation with Stations,    DEMNAS,  HEC-RAS, Satellite Imagery, Sentinel 2.